Child Poverty in English-Speaking Countries - John Micklewright (Institute for the Study of Labor (IZA), 2004)
The paper considers child poverty in rich English-speaking countries – the US, Canada, Australia, New Zealand, the UK, and Ireland. Do all these countries really stand out from other OECD countries for their levels of child poverty, as is sometimes assumed? And what policies have they adopted to address the problem? ?Poverty? is interpreted broadly and hence the available cross-national evidence on educational disadvantage and teenage births is considered alongside that on low household income. Likewise, discussion of policy initiatives ranges across a number of areas of government activity.
Keywords: J13; H53; I32; 330; poverty; children; English-speaking countries; Kinder; Armut; Familienleistungsausgleich; Vereinigte Staaten; Kanada; Australien; Neuseeland; Grossbritannien; Irland